1995
DOI: 10.1007/bf02191704
|View full text |Cite
|
Sign up to set email alerts
|

Transgene inactivation inPetunia hybrida is influenced by the properties of the foreign gene

Abstract: Petunia mutant RL01 was transformed with maize A1 and gerbera gdfr cDNAs, which both encode dihydroflavonol-4-reductase (DFR) activity. The same Agrobacterium vector and the same version of the CaMV 35S promoter were used in both experiments. Transformation with the cDNAs resulted in production of pelargonidin pigments in the transformants. However, the A1 and gdfr transformants showed clearly different phenotypes. The flowers of the primary A1 transformants were pale and showed variability in pigmentation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 24 publications
2
39
0
2
Order By: Relevance
“…These results reconfirm that pelargonidin production is an effective way to change flower color toward orange or bright red, as shown previously in petunia (Elomaa et al 1995;Meyer et al 1987;Tanaka et al 1995;Tsuda et al 2004), tobacco (Nakatsuka et al 2007), and Osteospermum (Seitz et al 2007). Our results confirm that downregulation of the F3Ј5ЈH and F3ЈH genes is insufficient and that addition of a suitable the proper DFR gene is necessary to generate a metabolic flux toward pelargonidin.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…These results reconfirm that pelargonidin production is an effective way to change flower color toward orange or bright red, as shown previously in petunia (Elomaa et al 1995;Meyer et al 1987;Tanaka et al 1995;Tsuda et al 2004), tobacco (Nakatsuka et al 2007), and Osteospermum (Seitz et al 2007). Our results confirm that downregulation of the F3Ј5ЈH and F3ЈH genes is insufficient and that addition of a suitable the proper DFR gene is necessary to generate a metabolic flux toward pelargonidin.…”
supporting
confidence: 90%
“…intense flower color than the maize gene in petunia (Elomaa et al 1995). Downregulation of the F3ЈH gene and expression of the rose DFR gene in red petunia accumulating cyanidin results in an orange petunia producing pelargonidin (Tsuda et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar correlation is observed in plants where the win3.12T promoter directed the expression of the GUS reporter gene (Yevtushenko et al, 2004). Other reports have shown that transgene copy number can have positive (Gendloff et al, 1990;Elomaa et al, 1995), negative (Finnegan and McElroy, 1994), or no effect (Peach and Velten, 1991) on transgene expression. Although an increased copy number has often been associated with transgene silence (for review see Finnegan and McElroy, 1994), the highest number of transgene insertions in plants in this study had no inhibitory effect on the accumulation of CEMA transcripts.…”
Section: Discussionsupporting
confidence: 66%
“…The petals and anthers of the resultant transgenic petunia plants were salmon pink and contained pelargonidin (Tanaka et al, 1995). Elomaa et al (1995) concluded that the properties of the transgene itself strongly influenced the inactivation process.…”
Section: Introductionmentioning
confidence: 99%